The development of theory-informed participant-centred interventions to maximise participant retention in randomised controlled trials - Rumana Newlands; Eilidh Duncan; Shaun Treweek; Jim Elliott; Justin Presseau; Peter Bower; Graeme MacLennan; Margaret Ogden; Mary Wells; Miles D. Witham; Bridget Young; Katie Gillies (My University, 2022)
Background: A failure of clinical trials to retain participants can influence the trial findings and significantly impact the potential of the trial to influence clinical practice. Retention of participants involves people, often the trial participants themselves, performing a behaviour (e.g. returning a questionnaire or attending a follow-up clinic as part of the research). Most existing interventions that aim to improve the retention of trial participants fail to describe any theoretical basis for the potential effect (on behaviour) and also whether there was any patient and/or participant input during development. The aim of this study was to address these two problems by developing theory- informed, participant-centred, interventions to improve trial retention. Methods: This study was informed by the Theoretical Domains Framework and Behaviour Change Techniques Taxonomy to match participant reported determinants of trial retention to theoretically informed behaviour change strategies. The prototype interventions were described and developed in a co-design workshop with trial participants. Acceptability and feasibility (guided by (by the Theoretical Framework of Acceptability) of two prioritised retention interventions was explored during a focus group involving a range of trial stakeholders (e.g. trial participants, trial managers, research nurses, trialists, research ethics committee members). Following focus group discussions stakeholders completed an intervention acceptability questionnaire. Results: Eight trial participants contributed to the co-design of the retention interventions. Four behaviour change interventions were designed: (1) incentives and rewards for follow-up clinic attendance, (2) goal setting for improving questionnaire return, (3) participant self-monitoring to improve questionnaire return and/or clinic attendance, and (4) motivational information to improve questionnaire return and clinic attendance. Eighteen trial stakeholders discussed the two prioritised interventions. The motivational information intervention was deemed acceptable and considered straightforward to implement whilst the goal setting intervention was viewed as less clear and less acceptable.